The Risk-Taking Channel and Monetary Transmission Mechanisms in Indonesia - Pristanto Silalahi; Telisa Aulia Falianty (Jurnal Ekonomi dan Studi Pembangunan, 2023)
This study aims to analyze monetary and macroprudential policies through risk taking banks in Indonesia. The importance of risk-taking channel analysis in the transmission mechanism of monetary policy is that it is a newer route and is different from the bank lending channel that has been previously proposed in monetary policy theory. This risk-taking channel affects the supply of credit by banks through the bank's decision to channel credit based on changes in bank behavior in dealing with bank risk. The study also recognizes the impact of monetary and macroprudential policies and the role of the characteristics of banks, as well as macroeconomic conditions such as economic growth and inflation rates. The analytical method used is fixed effects through panel data in the period 2012-2019. This study uses 3 types of proxies to measure risk, first with the Z-score measurement method, second with the ratio of the number of risky assets to total assets and third, the ratio of the number of bad loans to total assets. The results of this study found that the impact of monetary policy and macroprudential policy significantly affects bank risk. In addition to the main variables, this study also uses GDP growth and inflation variables as control variables for macroeconomic conditions that significantly effect on bank risk, liquidity, and bank size variables as control of bank characteristics which also significantly affect bank risk. So, it can be concluded that the risk-taking channel exists in Indonesia’s banking.